Meta-analysis of Xiaoyao formula as an adjuvant therapy for treating postpartum depression - Liu, Jing; Rong, Anna; Wang, Fei (Frontiers in Psychiatry, 2025)
BackgroundXiaoyao Powder/Pill, as a classical Chinese herbal formula, has been widely used for treating depression. This meta-analysis aims to evaluate the effectiveness of Xiaoyao formula (XYF) as an adjuvant therapy for treating postpartum depression.MethodsWe searched studies indexed in international databases (Cochrane Library, Embase, and PubMed) and Chinese databases (SinoMed, CNKI, and Wanfang). Randomized controlled trials (RCTs) assessing the efficacy of XYF in combination with Western therapy compared to Western therapy alone for treating postpartum depression were eligible. The total response rate was defined as a reduction of more than 25% in depression scores, while clinical recovery was defined as a reduction of more than 75% in depression scores.ResultsOur analysis included ten RCTs comprising 810 women. The combination of XYF and Western therapy led to a significant improvement in the total response rate (risk ratios [RR] 1.17; confidence intervals [CI] 1.08-1.26) and the clinical recovery rate (RR 1.56; 95% CI 1.27-1.91) compared to Western therapy alone. Additionally, XYF as an adjuvant therapy also significantly decreased Hamilton Depression Scale scores (standard mean difference [SMD] -1.69; 95% CI -2.37 to -1.01).ConclusionsAdjuvant treatment with XYF can effectively alleviate depression in postpartum women. However, further well-designed RCTs are necessary to validate these findings, as the current evidence remains uncertain.